Correlation of Long Term Proton Pump Inhibitors (PPI) Use with Iron and Vitamin B12 Deficiency Anaemia (Bangladesh Medical Journal, 2021)
The Suppression of gastric acid by long term use of PPI may decrease iron and vitamin B12 absorption and might be causing iron and vitamin B12 deficiency anaemia.  This comparative cross-sectional study was conducted among patients with peptic ulcer disease from November 2017 to March 2020; attending in the Internal Medicine department of Bangabandhu Sheikh Mujib Medical University (BSMMU). A total of   80  patients were included and divided into group-A (PPIs user) and group-B (non-PPI user), each group containing 40 patients each. The group-A  included patients who were taking PPIs for more than one year and  aged from  18 to 70 years and group-B the control group who were not taking PPIs for atleast 1(one) year. The data were analysed by Statistical Package for the Social Sciences (SPSS) version 20.0 (SPSS Inc., Chicago, IL, USA).The study shown that male were  18(45%) and 19(47.5%) in group A and B respectively  and female were 22(55%) and 21(52.5%) in group A and B respectively. The mean age of male and female was (year) 45.35 ± 12.46, 44.85 ± 15.24, respectively. Most of the patient took omeprazole 62.5% follwed by, esomeprazole 20%, pantoprazole 12.5%, rabeprazole 5%. About 47.5% of the patient took PPI for more than 2 years, and 52.5% took between 1-2 years. The mean (±SD) haemoglobin (Hb) level was 10.93±2.00 g/dl amongst  group-A and  13.16±1.68g/dl in group-B, the difference is statistically significant (P